Examining Determinants of Household Vulnerability in Nepal: Descriptive Statistics Analysis of Flood Disasters (Patan Pragya, 2022)
This study examines determinants of household vulnerability at the community level based on primary data by descriptive statistics. As a result, multiple variables that are awareness, traditional knowledge, and preparedness, nature of asset, income & information are its determinants. These variables are themselves vulnerable. In the correlation result, agro loss, family size and income of household are significant. Agro-loss is a major determinant one. About 70 percent households are vulnerable in which 23.75 percent households are extremely vulnerable. Therefore, adaptation capacity should be improved to reduce vulnerability. This study is expected to contribute in the execution of disaster risk reduction management (DRRM) in the study area of Nepal.